Magnetic hydrogel beads based on PVA/sodium alginate/laponite RD and studying their BSA adsorption. (20th August 2016) - Mahdavinia, Gholam Reza; Mousanezhad, Sedigheh; Hosseinzadeh, Hamed; Darvishi, Farshad; Sabzi, Mohammad
Highlights: Magnetic PVA/alginate beads with high stability under buffered solutions prepared. The magnetic nanoparticles were immobilized on laponite RD. The magnetic hydrogel beads showed pH-dependent swelling behavior. The maximum adsorption capacity of beads for BSA was achieved at pH 4.5. Abstract: In this study double physically crosslinked magnetic hydrogel beads were developed by a simple method including solution mixing of sodium alginate and poly(vinyl alcohol) (PVA) containing magnetic laponite RD (Rapid Dispersion). Sodium alginate and PVA were physically crosslinked by Ca 2+ and freezing-thawing cycles, respectively. Magnetic laponite RD nanoparticles were incorporated into the system to create magnetic response and strengthen the hydrogels. All hybrids double physically crosslinked hydrogel beads were stable under different pH values without any disintegration. Furthermore, adsorption of bovine serum albumin (BSA) on the hydrogel beads was investigated on the subject of pH, ion strength, initial BSA concentration, and temperature. Nanocomposite beads exhibited maximum adsorption capacity for BSA at pH = 4.5. The experimental adsorption isotherm data were well followed Langmuir model and based on this model the maximum adsorption capacity was obtained 127.3 mg g −1 at 308 K. Thermodynamic parameters revealed spontaneous and monolayer adsorption of BSA on magnetic nanocomposites beads.